The Dialectic of the Rome Statute: Oppositeness and Unity of the Complementarity and Corrective Function of the International Criminal Court (Italian Review of Legal History, 2024)
Under international law, it is each State’s obligation and responsibility to recognize the most serious crimes committed against the international community, as well as criminalize and conduct effective investigations and prosecution of them. The establishment of a permanent International Criminal Court, whose well-known complementarity principle is one of its central tenets, has finally emerged as a pillar in the fight against the impunity of international crimes. The article derives from various implementations a test for determining the characteristics and functions of the correction function of international law, thus presents the argument that the Rome Statute’s complementary role provides a corrective function.